2014
DOI: 10.1002/ana.24114
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of low spinal muscular atrophy carrier frequency in sub‐Saharan Africa

Abstract: ObjectiveSpinal muscular atrophy (SMA) is one of the most common severe hereditary diseases of infancy and early childhood in North America, Europe, and Asia. SMA is usually caused by deletions of the survival motor neuron 1 (SMN1) gene. A closely related gene, SMN2, modifies the disease severity. SMA carriers have only 1 copy of SMN1 and are relatively common (1 in 30–50) in populations of European and Asian descent. SMN copy numbers and SMA carrier frequencies have not been reliably estimated in Malians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…Studies performed on various American population groups, showed an unusually high frequency of multiple copies of SMN1 in the African American population when compared to other populations (Hendrickson et al, 2009;Sugarman et al, 2012). A study performed on unaffected individuals from various sub-Saharan African populations (Kenyan, Malian and Nigerian) confirmed this observation and showed a higher frequency of multiple copies of SMN1 and deletions of SMN2 than European populations (Sangaré et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Studies performed on various American population groups, showed an unusually high frequency of multiple copies of SMN1 in the African American population when compared to other populations (Hendrickson et al, 2009;Sugarman et al, 2012). A study performed on unaffected individuals from various sub-Saharan African populations (Kenyan, Malian and Nigerian) confirmed this observation and showed a higher frequency of multiple copies of SMN1 and deletions of SMN2 than European populations (Sangaré et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
“…A major limitation of previous quantitative studies of the SMN region performed in African-American (Hendrickson et al, 2009;Sugarman et al, 2012) and sub-Saharan African populations (Sangaré et al, 2014) was that CNV analysis was performed in unaffected individuals, with the exception of prenatal screening performed by Sugarman et al This study focuses on comparing CNVs in black individuals who are negative for SMA (N/N b ) to identify non-pathogenic CNVs as well as patients with known homozygous SMN1 and SMN2, exon 7 deletions (M 1 /M 1 b and M 2 /M 2 b , respectively) and patients who are clinically suggestive of SMA (U/U b ) to delineate potential pathogenic CNVs.…”
Section: Discussionmentioning
confidence: 99%
“…SMA is an autosomal recessive disease and is a leading genetic cause of infant death worldwide with an incidence of 1 in 6000–10,000 births (Pearn, 1978; Cuscó et al., 2002). The carrier frequency for SMA is 1:25–50 in most populations (Ben-Shachar et al., 2011; Su et al., 2011; Sugarman et al., 2012; Lyahyai et al., 2012) though it is lower for some ethnicities (Zaldívar et al., 2005; Labrum et al., 2007; Hendrickson et al., 2009; Sangaré et al., 2014). SMA results from the loss or mutation of SMN1 ( survival motor neuron 1 ; OMIM #600354) on chromosome 5q13 (Lefebvre et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is a leading genetic cause of infant and early childhood mortality across the world with an incidence of 1 in ~10,000 live births (Pearn 1978; Cuscó et al 2002; Sugarman et al 2012). The carrier frequency for SMA ranges from 1:25 to 1:50 (Zaldívar et al 2005; Labrum et al 2007; Hendrickson et al 2009; Ben-Shachar et al 2011; Su et al 2011; Sugarman et al 2012; Lyahyai et al 2012; Sangaré et al 2014). While SMA is primarily a disorder affecting motor neurons, other cells are affected by this disease (Shababi et al 2014).…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%